Dataset from "Sustainable Lignin–Acrylonitrile Copolymers via Aqueous Free Radical Polymerization for Carbon Fiber Development" - Marta C. Lourenço (22748472) (2025)
Dataset from the manuscript "Sustainable Lignin–Acrylonitrile Copolymers via Aqueous Free Radical Polymerization for Carbon Fiber Development".